Cupholder for confined space - BANIAK, GRZEGORZ H (1996)
A container holding assembly (10, 10') for a vehicle includes a housing (12, 12') having an elongated vertical opening (14, 14') therein. A support member (16, 16') is movable into and out of the opening (14, 14'). The support frame (16, 16') includes a U-shaped frame (18, 18') supporting a rotatable container holder (22, 22'). The container holder (22, 22') pivots between a retracted position within the housing (12, 12') with the container holder (22, 22') planar with the U-shaped frame (18, 18') and an extend position with the container holder (22, 22') transverse to the frame (18, 18').